Advances in Nanofiber composites and Thermosets - Patil, Shivendra; Nikhade, Rajat; Jaju, Krishna; Tripathi, Atul; V K, Abitha; Rane, Ajay Vasudeo (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Advancement is a result of recurring efforts beyond expectation‖. Nanofibers are an excitingmaterials defined as fibers having diameter less than or equal to 100 nm. When we deal with Nanolevelthe conditions required are different compared to micro-level. The dispersion of nanofiller isdifficult because of orientation effect and less aspect ratio. Nanofibers exhibit special propertiesmainly due to extremely high surface to weight ratio compared to other nonwoven fibers. Lowdensity, large surface area to mass, high pore volume, and tight pore size make nanofiberappropriate for making membranes as filtration applications. Those properties will be helpful inameliorating the conventional solar cells, supercapacitors and battery separators. The mostimportant property; which is high surface area makes it worthful in applications described above.